Extravasation and outcomes in computed tomography and angiography in patients with pelvic fractures requiring transcatheter arterial embolization: A single-center observational study. Issue 5 (27th May 2022) - Nakajima, Kento; Yamaguchi, Keishi; Abe, Takeru; Taniguchi, Hayato; Mizukami, Saori; Sekikawa, Zenjiro; Takeuchi, Ichiro
Abstract : Even in the absence of extravasation in the pelvic region on contrast-enhanced computed tomography, angiography or transcatheter arterial embolization may still be necessary. Abstract : BACKGROUND: Extravasation on contrast-enhanced computed tomography (CECT) is a helpful indicator of the need for transcatheter arterial embolization (TAE) for pelvic fractures. However, previous reports were inconsistent on cases in which angiography is necessary, even though there is no extravasation on computed tomography. This study aimed to describe and analyze the contradictory findings in cases where extravasation is observed on angiography but not on CECT, to contribute to improved management of patients with pelvic fractures. METHODS: This was a retrospective single-center study. Patients with pelvic fractures who underwent CECT and TAE between 2014 and 2020 were included. We classified the patients into three groups: CECT and angiography with extravasation (CT+Angio+), CECT with no extravasation and angiography with extravasation (CT−Angio+), and CECT with extravasation and angiography without extravasation (CT+Angio−). RESULTS: A total of 113 patients were included in the study: the CT+Angio+ group had 54 patients, CT−Angio+ group, 47; and CT+Angio− group, 12. The CT−Angio+ group had a significantly longer time from arrival to CECT than the CT+Angio+ group (27 minutes vs. 23 minutes, p < 0.05). The CT−Angio+ group had significantly more blood transfusions (fresh frozen plasma, platelets) within 24 hours than the CT+Angio− group did ( p < 0.05), and ventilator management days ( p < 0.05) and intensive care unit stays ( p < 0.05) were significantly longer. CONCLUSION: There was no significant difference in outcomes among the three groups. There was no difference in severity, transfusion volume, or mortality in patients with pelvic fractures needing TAE, classified as CT−Angio+, compared with that of CT+Angio+ patients. Even in the absence of extravasation in the pelvic region on CECT, angiography or TAE may still be necessary. LEVEL OF EVIDENCE: Therapeutic/Care Management, Level IV. Abstract :